KAJIAN MATEMATIKA EKONOMI: ANALISIS KONSEP DAN PENERAPANNYA DALAM KEHIDUPAN SEHARI-HARI - Ayu Lestari; Riskayani Jaida; Nabila Rahmawati; Nur Yuliany (LPPM Institut Ahmad Dahlan Probolinggo, 2026)
Mathematical economics is a branch of science that integrates mathematical concepts in the analysis of various economic problems. In everyday life, economic activities such as buying and selling, calculating profits, discounts, interest, and financial decision-making are inseparable from the application of mathematical concepts. This article aims to examine the basic concepts of mathematical economics and analyze their application in everyday life. The research method used is a literature study by reviewing various sources such as books, scientific journals, and other relevant references. The results of the study indicate that the concept of linear functions is used in the analysis of demand and supply, the concept of social arithmetic is applied to the calculation of discounts and profits, while the concept of interest and series is used in the calculation of investment and savings. Furthermore, an understanding of mathematical economics helps individuals make economic decisions rationally, effectively, and efficiently. Thus, mathematical economics plays a crucial role in improving people's economic analysis skills in everyday life.